Tricolor R/G/B Laser Diode Based Eye-Safe White Lighting Communication Beyond 8 Gbit/s - Tsai-Chen Wu (Nature Portfolio, 2017)
Abstract White light generation by mixing red, green, and blue laser diodes (RGB LDs) was demonstrated with Commission International de l’Eclairage coordinates of (0.2928, 0.2981), a correlated color temperature of 8382 K, and a color rendering index of 54.4 to provide a maximal illuminance of 7540 lux. All the white lights generated using RGB LDs were set within the risk group-1 criterion to avoid the blue-light hazard to human eyes. In addition, the RGB-LD mixed white light was diffused using a frosted glass to avoid optical aberration and to improve the performance of the lighting source. In addition, visible light communication (VLC) by using RGB-LD mixed white-light carriers and a point-to-point scheme over 1 m was performed in the directly modulated 16-QAM OFDM data format. In back-to-back transmission, the maximal allowable data rate at 10.8, 10.4, and 8 Gbps was determined for R, G, and B LDs, respectively. Moreover, the RGB-LD mixed white light-based indoor wavelength-division multiplexing (WDM)-VLC system yielded a total allowable transmission data rate of 8.8 Gbps over 0.5 m in free space. Such a high-speed RGB-LD mixed WDM-VLC system without any channel interference can be used to simultaneously provide data transmission and white lighting in an indoor environment.